Can Tourism and Natural Parks Coexist? Comparison of Europe, China, and the United States of America - Fabio Fratini; Silvia Rescic; Loredana Luvidi (Geosciences, 2022)
Over the years, people’s interest in protecting the natural environment and its resources has increased significantly. In this context, natural parks have become a new tourist destination, which has grown exponentially in recent decades and developed into mass tourism. This made it necessary to realize adequate infrastructures (roads, accommodation facilities reception, etc.) to allow visitors to enjoy parks. A recent trip to China made it possible to observe how this type of tourism has developed and raised some concerns and the need to understand whether this phenomenon is also present in other countries. In particular, this research examines the infrastructures (roads, accommodation facilities, and visitor centres) of some parks in the United States and Europe to compare them with the Chinese experience. The analysis revealed a difference in the visiting facilities of European parks compared to those in China and North America. In fact, the management and fruition of European parks seem to have less impact on the territories because they make use of road networks and accommodation facilities already present in the territory and that are often present in small villages. While in the case of China and the USA, it has been necessary to build new visitor centres and accommodation facilities in territories that were often uninhabited.